PENGUATAN EDUKASI GIZI SEIMBANG ANAK USIA SEKOLAH MELALUI PENDEKATAN INTERAKTIF DAN PARTISIPATIF DI SD NEGERI 11 RAMBANG - Aurellia Rahma; Andini Zahrah; Anindya Rahma; M. Dzulfadli Fawwaz Dzaky; Olivia Berbelina Balubun; Rahmi Fitri J (PARIPALAKA SRIWIJAYA, 2025)
Field Learning Experience (PBL) in Baru Rambang Village is part of the implementation of educational and promotive activities in an effort to improve public health. One of the work programs implemented is education about Isi Piringku and Cuci Tangan Pakai Sabun (CTPS) aimed at students of Elementary School 11 Rambang. This activity aims to provide an early understanding of the importance of consuming nutritious, balanced food and clean living habits by washing hands to prevent disease. The method used in this activity is a participatory approach through interactive learning media such as educational games and illustrated posters. The results of the activity showed high student enthusiasm regarding the importance of a balanced food composition and hand hygiene. This program is expected to be the first step in forming a healthy lifestyle among